An empirical study of the extent of usage of quantitative techniques in Malaysian business firms - Ku-Mahamud, Ku Ruhana; M. Oktovia, Brigida (Universiti Utara Malaysia, 1995)
A study was conducted to examine the extent of usage of quantitative techniques and the adequacy of computers as support tools among Malaysian business firms. Results indicate that 98% of the respondents reported using one or more techniques. The lack of knowledge and familiarity among top management was the most common reason cited for low use. Findings of this study are compared to a comparable survey in the United States and Hong Kong